Chemical and morpho-structural characterization of atmospheric aerosol (PM10 and PM2.5) in a city of São Paulo state, Brazil - Trevizan Franzin, Bruno (2021)
To access the sources of air pollutants is crucial to control atmospheric pollution in urban areas, minimizing human exposure. Particulate matter is a pollutant of great concern making its chemical and morpho-structural characterization of enormous importance. The present work aims at the characterization of atmospheric PM10 and PM2.5. Data of the aerosol mass concentration was correlated bymultivariate analysis with water-soluble ion fraction composition accessed by ion chromatography (IC), as well as with meteorological information and air mass backward trajectories. The gravimetric analysis presented average values 3 to 4 times higher than the guide values recommended by the World Health Organization (WHO). A morpho-structural analysis by SEM/FEG coupled to EDS was also carried out identifying the coarse fraction elements from minerals and from soil resuspension organic spherical particles that originated from combustion processes as well as Ti, associated with long-distance transportation. In the fine fraction, Zn with origin probably in tires and vehicle brakes was found. These origins were confirmed by the air masses’ backward trajectories obtained by the HYSPLIT model (NOAA). This study contributes to a better understanding of the complex composition of the particulate material in the atmosphere of Araraquara City, resulting from the combination of local and long-distance sources, and serves as a basis for the comparison with future studies related to the air quality at this and other regions in Brazil and in the world.